Penerapan Restorative Justice Pada Tindak Pidana Penganiayaan (LEGAL DIALOGICA, 2025)
The purpose of the research is to analyse the application of restorative justice in the crime of persecution committed in the jurisdiction of the district attorney's office of Gowa. This research is normative research conducted to find the real truth. The source of legal material used is the approach of legislation, legal theory, and rules that are in accordance with the settlement of disputes over the sale and purchase of goods through social media. This research method uses normative research methods. And the results of this study are the legal arrangements for the settlement of criminal offences with a restorative justice approach carried out by public prosecutors based on the provisions of article 5 paragraph 1 and paragraph 8 of prosecutor's regulation number 15 of 2020 concerning termination of prosecution based on restorative justice as an exercise of authority to streamline the law enforcement process provided by law by paying attention to the principles of fast, simple, and low cost justice to realise the success of case handling at the prosecution stage which is carried out independently for the sake of justice based on law and hatinuration. Recommendations in this study, in terms of the settlement of maltreatment cases in the restorative justice approach, public prosecutors need to implement the rules related to restorative justice better and practice in terms of case settlement so that they are in accordance with the ideals desired.Abstrak:Tujuan Penelitian untuk untuk menganalisis penerapan restorative justice pada tindak pidana kejahatan penganiayaan yang dilakukan di wilayah hukum kejaksaan negeri gowa. Penelitian ini adalah penelitian normatif dilakukan untuk menemukan kebenaran yang sebenarnya. Sumber bahan hukum yang digunakan ialah pendekatan peraturan perundang-undangan, teori hukum, dan aturan aturan yang sesuai dengan penyelesai sengketa terhadap jual beli barang melalui media sosial.. Metode penelitian ini menggunakan metode penelitian normatif. Dan hasil dari penelitian ini pengaturan hukum terhadap penyelesaian tindak pidana dengan pendekatan keadilan restoratif yang dilakukan oleh jaksa penuntut umum berdasarkan kepada ketentuan pasal 5 ayat 1 dan ayat 8 peraturan kejaksaan nomor 15 tahun 2020 tentang penghentian penuntutuan bersadasarkan keadilan restoratif sebagai pelaksanaan kewenangan untuk mengefektifkan proses penegakn hukum yang diberikan oleh undang-undang dengan memperhatikan asas peradilan cepat, sederhana, dan biaya ringan untuk mewujudkan keberhasilan penanganan perkara pada tahap penuntutuan yang dilaksanakan secara independen demi keadilan berdasarkan hukum dan hatinurasi. Rekomendasi dalam penelitian ini, dalam hal penyelesaian perkara tindak pidana penganiayaan dalam pendekatan restorative justice, jaksa penuntut umum perlu menjalankan aturan aturan terkait restorative justice lebih baik dan teiti menjalankan dalam hal penyelesaian perkara agar sesuai dengan cita-cita yang diinginkan yaitu berkedilan